Chamber study of PCB emissions from caulking materials and light ballasts. (October 2015) - Liu, Xiaoyu; Guo, Zhishi; Krebs, Kenneth A.; Stinson, Rayford A.; Nardin, Joshua A.; Pope, Robert H.; Roache, Nancy F.
Highlights: Emissions of PCBs from 13 caulk samples were tested in a micro-chamber system. Nineteen light ballasts from five manufacturers were tested in 53-L chambers. Emission rates of PCB congener from caulk and light ballasts were determined. Several factors that may have affected the emission rates were evaluated. New data and methods for ranking the primary sources of PCBs were provided. Abstract: The emissions of polychlorinated biphenyl (PCB) congeners from thirteen caulk samples were tested in a micro-chamber system. Twelve samples were from PCB-contaminated buildings and one was prepared in the laboratory. Nineteen light ballasts collected from buildings that represent 13 different models from five manufacturers were tested in 53-L environmental chambers. The rates of PCB congener emissions from caulking materials and light ballasts were determined. Several factors that may have affected the emission rates were evaluated. The experimentally determined emission factors showed that, for a given PCB congener, there is a linear correlation between the emission factor and the concentration of the PCB congener in the source. Furthermore, the test results showed that an excellent log-linear correlation exists between the normalized emission factor and the vapor pressure (coefficient of determination, r 2  ⩾ 0.8846). The PCB congener emissions from ballasts at or near room temperature were relatively low with or without electrical load. However, the PCB congener emission rates increased significantly as the temperature increased. The results of this research provide new data and models for ranking the primary sources of PCBs and supports the development and refinement of exposure assessment models for PCBs.